Improving the Cyclability and Rate Capability of Li4Ti5O12 Anode Material by Cu2+ and F− co‐Doping. Issue 5 (1st February 2023) - Kahrizi, Meisam; Kashani, Hamideh; Ghaffarinejad, Ali
Abstract: We report a new Li4 Ti5−x Cux O11.7 F0.3 (X=0.1, 0.15, 0.2, 0.25, 0.3) anodic material for use in Li‐ion batteries. These modified Li4 Ti5 O12 (LTO) materials were prepared by solid‐state method and calcination at 800 °C. The Li4 Ti4.75 Cu0.25 O11.7 F0.3 (LTCu0.25 OF0.3 ), among all samples, shows the best results in cyclability and rate ability. The LTCu0.25 OF0.3 delivers discharge capacities of 188.8, 180, 169.7, 151.2, 116, and 93.6 mAh g −1 at 0.1, 0.2, 0.5, 1, 3, and 5C, respectively. The capacity retention of LTO, LTOF0.3, and LTCu0.25 OF0.3 after 100 charge and discharge cycles at 1C is 90.8 %, 96.3 %, and 97.7 %, respectively. The enhancement in electrochemical performance of LTCu0.25 OF0.3 is attributed to the lower polarization and charge transfer resistance (15.5 Ω) and higher Li + diffusion coefficient (6.4×10 −7 cm 2 s −1 ) obtained by cyclic voltammetry (CV) and electrochemical‐impedance spectra (EIS) tests. This work indicates that Cu 2+ and F − have a synergistic impact on the electrochemical properties of LTO. Abstract : The common LTO anode of the Li‐ion battery was doped with Cu 2+ and F − ions, which improved the performance of this anode by decreasing the polarization, cell resistance, and charge transfer resistance